Government of corruption: the role of Malaysia government in the anti-corruption efforts - Abdul Manan, Abdul Faruq; Md Nor, Mohd Sabri; Adnan, Zatul Himmah; Ismail, Mohd Mahadee (Human Resource Management Academic Research Society, 2022)
There has been a different success story in fighting corruption in developing and developed countries. In recent years, corruption has become endemic and pervasive. Malaysia has been dubiously branded as a kleptocracy and has made headlines worldwide. This article examines factors that influence the outcome perceived in previous efforts to implement anti-corruption strategies by the government to combat corruption in Malaysia. Using a structured review process to examine existing text material comes from mundane secondary sources critically. The analysis shows that limitation of power by MACC to prosecute corruption cases and its institutional position under prime minister department that create agitation or potential being subject to influence or partisan. Furthermore, the low momentum in implementing anti-corruption reform and strategy as well as the deficiency in good governance such as free media, freedom of information act and whistle blower protection laws, suppressed public opinion in checking the official excesses. This article concludes governance of corruption in Malaysia at best minimum as evidenced in perception data and statistics from the government agency.